The Differential Effect of Toxoplasma Gondii Infection on the Stability of BCL2-Family Members Involves Multiple Activities - Carmen, John C.; Sinai, Anthony P. (Frontiers in Microbiology, 2011)
The regulation of mitochondrial permeability, a key event in the initiation of apoptosis is governed by the opposing actions of the pro- and anti-apoptotic members of the BCL2 family of proteins. The BCL2 family can be classified further based on the number of BCL-homology (BH) domains they encode. Pathogen mediated modulation of BCL2-family members play a significant role in their ability to affect the apoptotic pathways in the infected host cell. The protozoan parasite Toxoplasma gondii establishes a profound blockade of apoptosis noted by a requirement for host NFkappaB activity and correlating with the selective degradation of pro-apoptotic BCL2 family members. In this study we explore the potential activities associated with the inherent stability of the anti-apoptotic BCL2 as well as the selective degradation of the pro-apoptotic proteins BAX, BAD and BID. We find that multiple activities govern the relative stability of BCL2-family members suggesting a complex and balanced network of stability enhancing and destabilizing activities are perturbed by parasite infection. The data leave open the possibility for both parasite induced host activities as well as the direct consequence of parasite effectors in governing the relative levels of BCL2 proteins in the course of infection.